2021
DOI: 10.7759/cureus.16817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Thrombus Burden and Outcome in Acute Myocardial Infarction

Abstract: Background Cardiovascular manifestations are one of the most common complications in coronavirus disease 2019 (COVID-19) infection and are associated with increased mortality. However, the impact of COVID-19 infection on thrombus burden and the outcome of acute myocardial infarction (AMI) has not been studied. Methods This was a retrospective, observational study that included all adult patients (>18 years) diagnosed with AMI with or without COVID-19 infection. Epidemiological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The high thrombotic load in patients with AMI and COVID is known. In addition to the findings in other studies in the literature[ 14 , 15 ], there are also other important reports addressing this issue, such as a statement from the American College of Cardiology in which the authors concluded that patients with ST-segment elevation myocardial infarction and concurrent COVID-19 experienced a higher thrombotic burden than those without concurrent COVID-19[ 13 ].…”
Section: Discussionmentioning
confidence: 85%
“…The high thrombotic load in patients with AMI and COVID is known. In addition to the findings in other studies in the literature[ 14 , 15 ], there are also other important reports addressing this issue, such as a statement from the American College of Cardiology in which the authors concluded that patients with ST-segment elevation myocardial infarction and concurrent COVID-19 experienced a higher thrombotic burden than those without concurrent COVID-19[ 13 ].…”
Section: Discussionmentioning
confidence: 85%
“…In our study, there was a trend towards higher in-hospital mortality in the COVID-19 positive STEMI patients. Most of the studies have reported a very high in-hospital mortality (12%–34%) among COVID-19 positive STEMI patients 1 , 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 . One possible explanation for the relatively lower in-hospital mortality in our study is the younger age of our study population (mean age 57 years), 8–10 years lower than patients in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed AMI hospital admissions before the COVID-19 pandemic in Beijing, China, given its established impact on cardiovascular disease [18][19][20]. Data from 1 May 2014 to 31 December 2019 were obtained from the Beijing Municipal Health Commission Information Center.…”
Section: Data Gatheringmentioning
confidence: 99%